Enhancing student learning achievement using competency-based modules on basic competencies examining the characteristics of refrigerants and lubricating oils. Issue 4 (April 2020) - Suherman, A; Wiyono, A; Yayat, Y; Negara, R M H K; Berman, E T
Abstract: The purpose of this study was to determine the increase in student achievement using competency-based modules. The study was conducted on the subject of system and the installation of refrigeration with basic competencies examining the characteristics of refrigerants and lubricating oils. This study uses quasi-experimental research methods. Participants in this study were 60 students from the vocational high school in Bandung. The research instrument used was a test, which consisted of pre-test and post-test. Improved student achievement was analyzed using the concept of normalized gain (N-gain) based on pre test and post test score data. The results showed the use of competency-based modules can improve student learning achievement. The achievement of the post test scores of the experimental class students above the minimum completion criteria with an average post test score of 89.39, while the score of the control class was 72.42. Based on the N-Gain value there are differences between the experimental class and the control class which are 79.5 and 46.94, respectively. The use of competency-based modules has implications for improving student achievement to be more optimal. The content of interesting module materials can increase student motivation and activity in learning in the classroom.